(untitled) (World Bulletin of Public Health, 2025)
The continuous transformation of medical education necessitates the adoption of innovative pedagogical strategies to enhance the effectiveness of anatomy teaching. Anatomy, as a foundational discipline in medical training, requires not only the acquisition of theoretical knowledge but also the development of strong spatial thinking and clinical reasoning skills. This article aims to analyze modern pedagogical approaches and the integration of digital technologies in anatomy teaching, with a focus on improving learning outcomes among medical students. The study examines the use of interactive teaching methods, including problem-based learning, simulation-based education, three-dimensional digital models, virtual and augmented reality, and online learning platforms. Particular attention is given to the role of digital tools in increasing student engagement, motivation, and long-term knowledge retention. The findings indicate that the combined use of innovative pedagogical approaches and digital technologies significantly enhances the quality of anatomy education, promotes active learning, and facilitates the formation of clinically oriented competencies. The results of this study support the necessity of integrating modern educational technologies into anatomy curricula to meet the current demands of medical education and to prepare highly qualified healthcare professionals